Efektivitas Penggunaan Media Sosial, Promosi, dan Kualitas Layanan dalam Meningkatkan Pendapatan Salon Glowing Pacet Mojokerto (Studi Kasus Salon Glowing Pacet Mojokerto) - Buwana, Michael Adi; Setiawan, Erry; Joenarni, Elly; Dewianawati, Dwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Salon Glowing is a beauty salon located in Pacet Mojokerto. Social media is a means used by Salon glowing as a place to promote and display all forms of services. The purpose of this study is to determine the effect of the effectiveness of the use of social media, promotion, and service quality in increasing the income of the Glowing Pacet Mojokerto salon. The research method used in this study uses a quantitative research method by collecting data through surveys and analyses carried out using the distribution of questionnaires on visitors to Salon Glowing. The results showed that the effectiveness of the use of social media, promotion, and service quality on income was partially and simultaneously and together had a positive effect on the value of the regression coefficient (B) X1:0.192; X2:0.166; X3:0.183. For the three variables of the effectiveness of social media use (X1), Promotion (X2) and Service quality (X3) which have a dominant and significant relationship to Revenue (Y), the variables of the effectiveness of social media use (X1) can be seen from the regression coefficient value (β) of 0.329, T calculate x1 = 2.685 > t table = 1.987 and the sig value x1 0.009 <0.05. By understanding these factors, Salon Glowing at pacet was able to optimize their marketing strategy and improve efficiency in the use of social media.